Human Rights for Women's Development in Multidimensional: A Step towards Gender Equality in Education - Andrey Shastri (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
Women's educational human rights and gender equality is one of the burning topics nowadays. Following the gender equality framework proposed by United Nations in its Millennium Summit in 2000 declared "Gender equality and women empowerment". This present study tries to review gender equality for women in many aspects, including the major concern in this review, i.e., education and human right. After analyzing several documents in the net during the collection period, this study sees that women have achieved a lot. However, yes still they are lagging in terms of equality in education and human right. The fact showed women are far lagging and leave alone on the question of gender equality. The present paper explores and highlighted these issues as the central questions related to women's rights and also attempts to wrestle with the few challenges that faced by the women education system in India as a specific example. At last, this paper also try to highlight some strategy as to upgrade the status of women in society, ever since this study believes that Educating a woman will uplifts her life as well as the quality of the nation.